Small-nerve-fiber pathology in critical illness documented by serial skin biopsies - Skorna, Miroslav; Kopacik, Roman; Vlckova, Eva; Adamova, Blanka; Kostalova, Milena; Bednarik, Josef (Muscle & nerve, 2015)
INTRODUCTION: Small-fiber pathology can develop in the acute phase of critical illness and may explain chronic sensory impairment and pain in critical care survivors. METHODS: Eleven adult ischemic stroke patients in a neurocritical care unit were enrolled in an observational cohort study. Intraepidermal nerve fiber density (IENFD) in the distal leg was assessed on admission to the intensive care unit and 10-14 days later, together with electrophysiological testing. RESULTS: Of the 11 patients recruited, 9 (82%) had sepsis or multiple-organ failure. Median IENFD on admission (5.05 fibers/mm) decreased significantly to 2.18 fibers/mm (P < 0.001), and abnormal IENFD was found in 6 patients (54.5%). Electrodiagnostic signs of large-fiber neuropathy and/or myopathy were found in 6 patients (54.5%), and autonomic dysfunction was found in 2 patients (18.2%). CONCLUSION: Serial IENFD measurements confirmed the development of small-fiber sensory involvement in the acute phase of critical illness.
Keywords: polyneuropathy; Erythromelalgia; Male; longitudinální studie; Neurologic Examination; Critical Illness; Neural Conduction; critical illness; skin biopsy; biopsie; Aged; myopathy; mužské pohlaví; senioři; Electromyography; kůže; erytromelalgie; elektromyografie; Glasgow Coma Scale; Glasgowská stupnice kómat; nervové vedení; neurologické vyšetření; small fibers; lidé; kritický stav; ženské pohlaví; Skin; Humans; Longitudinal Studies; Biopsy; Female; lidé středního věku; Middle Aged